Technocracy and the Politics of Economic Decision Making during the Pre–Martial Law Period (1965–1972) - Encarnacion Tadem, Teresa S. (Archīum Ateneo, 2015)
Philippine technocracy during the martial law period (1972–1986) has been depicted in most of the literature as “apolitical.” Thisarticle argues that this depiction was not applicable to the pre–martial law period (1965–1972) when the Marcos administration’s technocrats, who went on to become the chief economic planners during the martial law period, exhibited “political sensitiveness” in economic policy making. This sensitivity helped pave the way for them to become part of the policy-making elite in the country and the Marcos leadership’s appendage in confronting intraelite squabbles.Keywords: technocracy • policy making • Marcos presidency •Cesar Virata • Placido Mapa Jr.